Problematika Pendidikan Sekolah Terisolir dalam Meningkatkan Kualitas Pembelajaran PAI (Studi Kasus di MtsS Nurul Falah Bangun Rejo Kecamatan Sangir Kabupaten Solok Selatan) - Amanda Wahyuni; Suprizen Suprizen; Rizal Safarudin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aim to determine how the process of isolated school education, what are the problems of isolated school education and how to solve the problems of isolated regional education in improving the quality of Islamic Religious Education learning (Case study at MTsS Nurul Falah Bangun Rejo, Sangir District, South Solok Regency). Based on the results of field research, the author can conclude that the quality of Islamic Religious Education learning at MTsS Nurul Falah Bangun Rejo is classified as good, this can be seen from, the teachers at MTsS Nurul Falah Bangun Rejo consist of two group, the first is honorary teachers and the second is civil servant teachers. However, between honorary teachers and civil servant teachers, the level of discipline is very different. This discipline can be seen from how the teacher carries out his duties as a teacher, including planning learning, implementing learning, assessing learning outcomes, guiding and training students and carrying out additional tasks given to him. With the existence of several room facilities that have been provided, students feel comfortable during the learning process.